Formulation and evaluation of gels containing coconut kernel extract for topical application - Wantanwa Krongrawa; Sontaya Limmatvapirat; Nushjira Pongnimitprasert; Paranee Meetam; Chutima Limmatvapirat (Elsevier, 2018)
The biological activity of coconut (Cocos nucifera L.) extracts from its kernels and various parts was reported by many previous studies, it is therefore believable that the extracts of its kernels might show some activities in topical formulations. Among several kernel extracts, the TC06 extract prepared by soaking the steamed coconut kernels in hot water showed the highest total phenolic content (6.98 ± 0.30 mg GAE/g extract) and the strongest antioxidant activity as determined using FRAP and DPPH methods with a reducing power value of 4.12 ± 0.16 mg AAE/g of extract and an SC50 value of 2.38 ± 0.14 mg/ml, respectively. In addition, this extract did not display any cytotoxic effects in the concentration range of 50-3200 µg/ml. Meanwhile, it revealed cytoprotective effects against t-BHP-induced cytotoxicity in HaCaT cells at concentrations higher than 400 µg/ml. The results of phytochemical investigations including a chemical color test, TLC, 1H NMR and FTIR suggested that the TC06 extract was mainly composed of flavonoids and terpenoids. Furthermore, the concentrations of heavy metals including As, Cd, Hg, and Pb in the TC06 extract were below permissible limits. According to the solubility, the TC06 extract was incorporated into gels using Carbopol Ultrez 21 as a gelling agent. The formulated gel containing 3% (w/w) TC06 extract was stable at 4 °C and 25 °C with 75% RH throughout the storage period. It was found that the Carbopol Ultrez 21-based hydroalcoholic gel containing an aqueous extract of coconut kernels exhibited antioxidant activities in the two assays and showed a sufficient consistency, a pleasing color, and a non-oily perception during the period of observation. Keywords: Coconut kernel, Extract, Gel, Antioxidant activity, Phytochemical screening